Surface-modified microbubbles (colloidal gas aphrons) for nanoparticle removal in a continuous bubble generation-flotation separation system. (1st December 2017) - Zhang, Ming; Guiraud, Pascal
Abstract: The treatment of nanoparticle (NP) polluted aqueous suspensions by flotation can be problematic due to the low probability of collision between particles and bubbles. To overcome this limitation, the present work focuses on developing an enhanced flotation technique using the surface-functionalized microbubbles – colloidal gas aphrons (CGAs). The CGA generator was adapted to be air flow rate controlled based on the classical Sebba system; thus it could be well adopted in a continuous flotation process. Cetyl trimethylammonium bromide (CTAB) and sodium dodecyl sulfate (SDS) were employed for CGA creation. Positively surface-charged CTAB-CGAs (∼44.1 μm in size) and negatively surface-charged SDS-CGAs (∼42.1 μm in size) were produced at the optimum stirring speed of 8000 rpm. The half-life of CGAs varied from 100 s to 340 s under the tested conditions, which was largely sufficient for transferring CGAs from bubble generator to flotation cell. The air flow led to less stable CTAB-CGAs but apparently enhanced the stability of SDS-CGAs at higher air flow rates. In the presence of air flow, the drainage behavior was not much related to the type of surfactants. The continuous CGA-flotation trials highlighted the effective separation of silica nanoparticles – the removal efficiencies of different types of SiO2 NPs could reach approximately 90%–99%; however, at equivalent surfactant concentrations, no greater than 58% of NPs were removed when surfactants and bubbles were separately added into the flotation cell. The SiO2 NPs with small size were removed more efficiently by the CGA-flotation process. For the flotation with CTAB-CGAs, the neutral and basic initial SNP suspension was recommended, whereas the SDS-CGAs remained high flotation efficiency over all investigated pH. The good performance of CGA-flotation might be interpreted: most of the surfactant molecules well covered/coated on the surfaces of stable CGAs and thus fully contacted with NPs, resulting in the efficient utilization of surfactants. Graphical abstract: Image 1 Highlights: CGAs, ∼43 μm in diameter, are continuously produced at controlled air flow rate. CGAs with ∼100 s' half-life time can be well pumped into a flotation device. Continuous CGA generation-flotation separation system remove 90%–99% of nanosilica. CGA-flotation remove much more nanosilica than DAF at equivalent surfactant dosages.